In the Face of Adversity Translating difference and dissent - Nolden, Thomas (Literature and Translation, 2023)
In the Face of Adversity explores the dynamics of translating texts that articulate particular notions of adverse circumstances. The chapters illustrate how literary records of often painful experiences and dissenting voices are at risk of being stripped of their authenticity when not carefully handled by the translator; how cultural moments in which the translation of a text that would have otherwise fallen into oblivion instead gave rise to a translator who enabled its preservation while ultimately coming into their own as an author as a result; and how the difficulties the translator faces in intercultural or transnational constellations in which prejudice plays a role endangers projects meant to facilitate mutual understanding. The authors address translation as a project of making available and preserving a corpus of texts that would otherwise be in danger of becoming censored, misperceived or ignored. They look at translation and adaptation as a project of curating textual models of personal, communal or collective perseverance, and they offer insights into the dynamics of cultural inclusion and exclusion through a series of theoretical frameworks, as well as through a set of concrete case studies drawn from different cultural and historical contexts. The collection also explores some of the venues that artists have pursued by transferring artistic expressions from one medium into another in order to preserve and disseminate important experiences in different cultural settings, media and arts.